PELAKSANAAN PEMBERIAN BANTUAN HUKUM PADA TINGKAT PENYIDIKAN BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA (KUHAP) DI WILAYAH HUKUM POLRES BUKITTINGGI - Anny Yuserlina (Ensiklopedia Social Review, 2021)
The provision of legal assistance at the level of investigation in the law of criminal justice in Indonesia is expected to provide maximum protection of the rights of life of suspects, especially those of weak and poor origin in the form of legal aid since the early stages of examination of suspects, Legal aid is not only interpreted as the right of the suspect since the investigation stage, but also as an obligation that must be fulfilled by every law enforcement apparat, especially investigators before starting an examination of suspects. Protection of the human rights of suspects since the stage of investigation is at least expected to be one of the factors that minimize the possibility of arbitrariness by law enforcement apparat and the possibility of irregularities in the application of criminal procedural legal procedures therefore examination at the level of investigation is important to get justice minimizing violations that can occur at any level that includes intimidation at the time of drafting News Of Inspection event so that apparat law enforcement stick to apparat law enforcement code of conduct and human rights values.